PERSEPSI MASYARAKAT TERHADAP KONDISI SOSIAL EKONOMI PASCA BERDIRINYA PERUSAHAAN PERKEBUNAN KELAPA SAWIT (Studi Kasus PT. Telen Prima Sawit di Kecamatan Muara Bengkal Kabupaten Kutai Timur) (Public Perception on the Socio-Economic Conditions Post-Establishment Plantation Company of Oil Palm (Case Study PT. Telen Prima Sawit in Subregency of Muara Bengkal Regency of East Kutai)) - ROBBY ARIS SUSANTO; MIDIANSYAH EFFENDI (JURNAL AGRIBISNIS DAN KOMUNIKASI PERTANIAN (Journal of Agribusiness and Agricultural Communication), 2019)
This research aimed to know the public perception on the socio-economic conditions post- establishment of oil palm plantation company (case study PT. Telen Prima Sawit). The research was done in Subregency of Muara Bengkal, Regency of East Kutai. This research was done from August until October 2016.  The number of samples was 44 respondents. Public perception on  the socio-economic conditions post-establishment of LCP oil palm plantations was known by doing analysis of data by descriptive.  The result of research shows that public perception on the socio-economic conditions post-establishment of oil palm plantation company PT Telen Prima Sawit in Subregency Muara Bengkal, Regency East Kutai  including in category positive  with an average score 52.70%.